Overall Survival and Related Factors of Patients Undergoing Breast-Conserving Surgery with Boost Through Interstitial Brachytherapy in a Cancer Center in Medellin, Colombia - González-Hernández, Liza María; Vásquez-Trespalacios, Elsa; Gallegos-Téllez, Erika Patricia; Corrales-Cruz, Lina María; Javier-Gallón, Luis; Naranjo, Ana María (South Asian Journal of Cancer, 2023)
Patients with breast cancer undergoing conservative surgery require management with radiotherapy to decrease the risk of recurrence. Moreover, the use of tumor bed boost in high-risk patients has shown an absolute reduction in the 10-year local recurrence risk from 23.9 to 13.5%. Therefore, this study aimed to estimate the overall survival of a group of patients undergoing conservative surgery with a boost through interstitial brachytherapy at a cancer center in Medellin, Colombia. A retrospective cohort study was performed, and records from 2014 to 2020 of patients with in situ or infiltrating breast cancer treated with a boost through interstitial brachytherapy were included. Univariate analysis was conducted to characterize the study population; median survival was calculated using the Kaplan–Meier method. Moreover, associations concerning survival were calculated with each of the factors independently. A total of 186 patients were included. Their overall survival was 93.5%, with a median survival of 79 months. The presence of negative hormone receptors, having two or more irradiated fields and having a locally advanced stage were factors associated independently with higher mortality. The overall survival of patients with in situ or infiltrating breast cancer was favorable and correlated with studies regarding intervention with a boost through interstitial brachytherapy and the factors associated with higher mortality, such as having a locally advanced stage.
Keywords: breast cancer; brachytherapy; overall survival; radiotherapy; treatment